Risk Factors of Colorectal Cancer Recurrence After Curative Resection Surgery: A Systematic Review and Meta-analysis - Hermansyah, Dedy; Muradi Muhar, Adi; Nuh Alhudawy, Muhammad; Anggia Paramita, Desiree; Nandita Firsty, Naufal (Reports of Radiotherapy and Oncology, 2022)
Context: According to the World Health Organization, colorectal cancer (CRC) is the third most prevalent cancer globally, with the highest mortality rate after lung cancer. Some studies predicted risk factors provoking CRC recurrence. However, no single study discussed CRC recurrence. Objectives: This study aimed to quantitatively estimate the influence of several risk factors toward early recurrence of CRC. Methods: We utilized four medical databases, including Pubmed, Cochrane, Wiley library, and ScienceDirect, and a range of literature searches between July to October 2020 with output study, odds ratio (OR), and some risk factors. We used PRISMA protocol along with several relevant keywords with NOS method was utilized to assess the quality of the study. Fixed- and randomized effect model were utilized to control each numerical analysis’ bias. Results: We found six studies that compared the risk factor of CRC recurrence after curative resection with curative-intention encompassing a total of 15.457 patients. We found seven risk factors of colorectal cancer recurrence, including vascular invasion (OR 2.3; IK95%: 01.56 - 3.4; P < 0.0001), depth of invasion (T stage) (OR 2.27; IK95%: 1.14 - 4.51; P = 0.02), pre-operative CEA serum (OR 2.24 IK95%: 1.57 - 3.2; P < 0.0001), post-operative CEA serum (OR 5.97 IK95%: 3.04 - 11.74; P < 0,0001), pre-operative CA19-9 serum (OR 3.03; IK95%: 1.74 - 5.25; P < 0.0001), and regional nodal metastasis (N stage) (OR 2.56; IK95% 1.41 - 4.62; P = 0.002). Conclusions: Risk factors of earlier CRC recurrence were diversely reviewed. The elevation of post-operative CEA serum was assumed as the main factor in this study; however, most of the studied parameters were statistically significant.